Assessment of Demand and Supply of Forest Products in Community Forests of Kaski District, Nepal - Thakuri, Bibek Jung; Malla, Aadesh Bikram; Khanal, Sharad (FORESTRY: Journal of Institute of Forestry, Nepal, 2024)
Community forests in Nepal are crucial for rural livelihoods, providing products like fuelwood, fodder, and timber. However, demand and supply imbalances threaten their sustainability. This study evaluates both the demand and supply of fuelwood, fodder, and timber in two CFs located in the Kaski district: Kurchinekharkha CF in Armala and Sisneridopare CF in Kaskikot. Data collection involved questionnaire surveys to estimate demand, while forest inventory and secondary data were used to estimate supply. A comparative analysis of Kurchinekharkha CF and Sisneridopare CF reveals critical disparities. Kurchinekharkha CF requires 23.9 tonnes of fodder annually, significantly less than Sisneridopare CF's 44.7 tonnes. Fuelwood demand mirrors at 0.88 tonnes per household in both areas, while timber demand is negligible in Kurchinekharkha CF but reaches 2.55 m³ in Sisneridopare CF, used mainly for livestock sheds. Despite Kurchinekharkha CF boasting a higher growing stock (114.94 m³/ha) compared to Sisneridopare CF (70.87 m³/ha), supply deficits persist. Fuelwood supply covers a mere 21.16% and 18.42% of demand, respectively. Fodder supply is severely limited, meeting only approximately 10% of demand in both forests, due to short collection periods and limited species. Timber supply remains near-zero due to regulations and lack of awareness. Demand drivers include household size, livestock holdings, and alternative energy access. While community forestry has benefited from forest regeneration, considerable supply gaps require adaptive strategies. Recommendations include promoting multipurpose tree species, integrating fodder plantations, and revising harvesting policies to better harmonize conservation with livelihood needs.